Factors Affecting Customers Satisfactionof Chooks to Go at Novaliches Quezon City: An Analysis for the Effectivity of an Organization: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today's fast-paced world, people are too busy to leave their homes or offices to purchase their favourite foods. Food delivery services have gained popularity, enabling customers to order from restaurants and deliver them to their doorstep. Many food ordering apps, such as GrabFood, Toktok, Delivery Guy PH, and FoodPanda, have also emerged, making it even easier for people to order food online. Even well-known fast-food chains and restaurants, such as McDonald's, Jollibee, Shakey's, and Greenwich, have created food ordering apps. The COVID-19 pandemic has greatly impacted businesses of all sizes in Bagong Silang, North Caloocan City. Due to the pandemic, many establishments have closed as people choose to stay at home to prevent the spread of the virus. As a result, food delivery services have become increasingly popular, allowing businesses to continue operating and selling their products online. To better understand the food delivery industry in Bagong Silang, North Caloocan City, a qualitative research study was conducted involving 50 food delivery riders. The study used purposive sampling and gathered information through survey questionnaires, observations, and interviews. The data was analyzed using statistical tools, including frequency, percentage, weighted mean, and ranking. The study found that most food delivery riders in Bagong Silang are male, aged between 25-28 and have job experience of two years or more. They typically work 1-5 or 6-11 hours daily. When assessing food delivery services, riders ranked a high hourly salary, clean and safe delivery equipment, and delicious food as their top priorities. They also value flexibility in accommodating customers' requests, the safety of the service provider, and the availability of delivery apps with GPS monitoring. The researchers found that the main challenges food delivery services face during the new normal are fake bookings, unstable oil prices, and late cancellations upon delivery. In conclusion, food delivery services have become essential to modern life, especially during the COVID-19 pandemic. Prioritizing the safety and satisfaction of customers and service providers is crucial to ensure the success of these services. By addressing the industry's challenges and implementing the suggestions of food delivery riders, businesses can continue to thrive in the new normal.
Keywords: Sales performance; Demands; Overall satisfaction; Convenience